Ionizing vs collisional radiation damage in materials: Separated, competing, and synergistic effects in Ti3SiC2. (July 2019) - Hanson, William A.; Patel, Maulik K.; Crespillo, Miguel L.; Zhang, Fuxiang; Zinkle, Steven J.; Zhang, Yanwen; Weber, William J.
Abstract: Comparison between intense radiation environments present in nuclear reactors and charged particle beams is necessary for evaluating next generation fission and fusion reactor materials. However, these two irradiation environments encompass different proportions of ionizing and collisional phenomena, so exploring the different energy loss pathways is needed for appropriate analysis. Using the candidate Mn+1 AXn phase, Ti3 SiC2, as a test case, this work separates the effects of electronic and nuclear energy loss during ion irradiation, through a combination of 4  MeV Au, 17  MeV  Pt, and 14  MeV Cl ion irradiations to examine the effects independently and systematically recombine them. Nuclear energy loss (elastic collisions) is found to be primarily responsible for the formation of a face-centered-cubic phase with anti-site defects, while intense electronic energy loss (ionization) exacerbates the effect and increases lattice strain. Further, these dissipation pathways are found to be competing or synergistic depending on their ionization and collisional ratio. Graphical abstract: Image 1